94-LB: A Phase 1, Double-Blind, Placebo-Controlled Multiple Escalating Dose Study of RGT-075 Novel Small-Molecule Oral GLP-1 Receptor Agonist in Adults with Type 2 Diabetes - PIRNER, MARK A.; LIN, JING; LIU, FENG; YAO, LILI; ZETTLER, MARJORIE E.; VALACER, DAVID J. (Diabetes (New York, N.Y.), 2022)
Background: RGT-075 is a small-molecule oral GLP-1 receptor agonist (GLP1RA) in clinical development. RGT-075 (15-280 mg) was well-tolerated by healthy adults in a prior phase 1 single ascending dose study. Phase 1 multiple-ascending dose study of RGT-075 in adults with type 2 diabetes (T2DM) results are presented. Methods: A Phase 1, randomized, double-blind, placebo-controlled, inpatient study planned multiple daily doses of RGT-075 or matching placebo (6 active/2 placebo per cohort) for up to 28 days in T2DM patients (baseline HbA1c 6-10.5% and concomitant metformin >500 mg/d) . An adaptive study design permitted dose and titration adjustments. Assessments included safety (primary) , PK, and exploratory efficacy changes in HbA1c, fasting plasma glucose (FPG) , continuous glucose monitoring time in range (CGM-TIR) , mixed-meal tolerance test MMTT, and body weight (BW) . Results: Four Cohorts enrolled 36 patients (56%F/44%M; mean age 55yF/61yM) to receive ([Starting Dose]→[Titration Duration]→[Target Dose]) : Cohort 1 [60 mg][ no titration][60 mg]; Cohort 2 [30 mg][10 d][120 mg]; Cohort 3 [15 mg][20 d][180 mg]; Cohort 4 [15 mg][28 d][45 mg]. Adverse events (AEs) were reported by most subjects (100% C1 + C2; 88% C3; 83% C4; 78% pooled placebo) . Most AEs were of mild severity, drug-related for RGT-075 groups, and predominantly GI with no serious AEs or deaths. Baseline HbA1c was highly variable (7.2-9.0%) ; HbA1c mean changes from baseline ranged -0.6 to -1.2% across RGT-075 doses vs. -0.37% with placebo and correlated with FPG, CGM-TIR and MMTT results. BW mean change ranged -2.3 to -4.5 kg across RGT-075 doses vs -1.1 kg with placebo. RGT-075 plasma exposures increased as the dose levels increased. Conclusion: RGT-075 GLP1RA oral small molecule (15-180 mg/day) up to 28 days was safe and QD dosing showed promising exploratory efficacy trends despite high baseline variability and short treatment duration.